Hybrid Ag nanocone–Al2O3/Si nanopillar periodic array for broadband anti-reflection - Xiangyao Luo; Wen Sun; Zichen Xiong; Yue Chang; Wenyi Ren; Xinyu An; He Wang; Hongchang An (Discover Nano)
Abstract In this paper, a periodic array of Ag nanocones and Al2O3/Si nanopillars (AgNCs–Al2O3/SiNPs) deposited on a semiconductor substrate is designed, and their anti-reflection property is investigated systematically using the finite difference time domain method (FDTD). The obtained results show that the designed structure achieves a weighted reflectance as low as 1.99% over a broad spectral range of 400–1100 nm. The anti-reflection mechanism of the AgNC–Al2O3/SiNP array is elucidated through calculations of the scattering cross-section and electric field distribution of the AgNC array. The localized surface plasmon resonance (LSPR) effects of AgNC array, together with the multiple scattering and reflection effects of the SiNP array, can reduce the reflectance to some extent. Furthermore, the introduction of Al2O3 spacer layer leads to an additional decrease in reflectivity. In addition, the reflective properties of three alternative metal nanocones (Al, Cu, and Au), combined with the Al2O3/SiNP array on a Si substrate, are evaluated. Among these composite structures, the CuNC–Al2O3/SiNP array exhibits the lowest reflectivity of 1.66%. This study enriches the localized surface plasmon model and provides a theoretical foundation for the design of plasmonic solar cells and other optoelectronic devices requiring low reflectivity.